The Essence of Teachers and Ideal Islamic Religion Teachers: Thought of Ki Hajar Dewantoro, KH. Ahmad Dahlan, KH. Hasyim Asy'ari, Hamka, and Maria Montessori - Lilik Kholisotin; M. Teguh Ciptadi; Faridi Faridi; Tobroni Tobroni (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research investigated Ki Hajar Dewantoro, KH. Ahmad Dahlan, KH. Hasyim Asy'ari, Hamka, and Maria Montessori viewed about the essence of teachers and ideal Islamic Religious Education (PAI) teachers. By using review literature approach, this research showed systematic and focused research methodology. First, research identified research problem and searched relevant literature source. Then literature sources were selected and evaluated based on inclusion and quality criteria. Data were collected and analysed to answer research problem. The view of Ki Hajar Dewantoro emphasized students' freedom, creativity and spirituality, with PAI teachers stimulating spiritual values and inter-religious tolerance. KH. Ahmad Dahlan proposed moderate and inclusive Islamic education, with PAI teachers who teached Islamic values in balanced and as model. KH. Hasyim Asy'ari saw knowledge, wisdom and noble moral in Islamic education, with criteria of professional, loving, authoritative, look after themselves, kept working, good teaching and broadminded PAI Teachers. Hamka initiated comprehensive understanding of religion, involving all aspects of life, and created responsible human. Maria Montessori emphasized experience-based approach, where PAI teachers created learning environment that supported students' exploration, creativity and direct experience. This research result summarized the conception of ideal PAI teachers and teachers, including freedom, creativity, spirituality, moderation, science, wisdom, noble morals, comprehensive understanding of religion, and experience-based approach. These findings gave deep insight into the importance of holistic education that configurated the character of young generation who character and responsibility.